Nb(V)-containing saponite: A versatile clay for the catalytic degradation of the hazardous organophosphorus pesticide paraoxon under very mild conditions - Stefano Marchesi; Stefano Econdi; Geo Paul; Fabio Carniato; Leonardo Marchese; Matteo Guidotti; Chiara Bisio (Heliyon)
A synthetic saponite clay containing structural Nb(V) metal centres (NbSAP) was investigated in the abatement of paraoxon-ethyl, an anti-cholinergic organophosphorus pesticide, under mild conditions (neutral pH, room temperature and ambient pressure) in heterogenous phase, without additional basic additives. The material was selected according to its high surface acidity and ease of preparation through a one-step hydrothermal synthesis. The presence of Nb(V) ions played a crucial role in efficiently catalysing the degradation of aggressive chemical substrates. A niobium(V) oxide with very low surface acidity was also tested as a reference material. The study employed a multi-technique approach to monitor the pesticide degradation pathway and by-products formed during abatement experiments in polar non-protic and aqueous solvents. Notably, in water, the concentration of paraoxon-ethyl significantly decreased by 82 % within the first hour of contact with the clay. Additionally, NbSAP demonstrated a good performance after three repeated catalytic cycles and subsequent reactivation.